Post weld heat treatment of inconel alloys - Chew, Benjamin Xuan Zheng (2017)
In this report, we would be investigating the optimization of vacuum induction brazing with Nickel based filler (AMS4777) on Inconel 718. The focus of this investigation will be on the effects of tensile strength, due to variations in temperature and soak time during brazing. Finally, we will conclude with a preliminary 3D Finite Element Analysis by COMSOL Multiphysics, for heat simulation and modelling.